2022
DOI: 10.3390/biomedicines10071762
|View full text |Cite
|
Sign up to set email alerts
|

Hyperreactivity of Salivary Alpha-Amylase to Acute Psychosocial Stress and Norepinephrine Infusion in Essential Hypertension

Abstract: It is unknown whether the observed general physiological hyperreactivity to acute psychosocial stress in essential hypertension also extends to salivary alpha-amylase (sAA), a surrogate sympathetic nervous system marker. Here, we investigated sAA reactivity to acute psychosocial stress in essential hypertensive males (HT) as compared to normotensive controls (NT). To shed light on underlying mechanisms, we moreover tested for sAA reactivity following a standardized norepinephrine (NE) infusion. We hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…In the hitherto only study investigating sAA reactivity to AMS in EHT, we recently found that HT exhibit greater sAA reactivity to the TSST as a strong mental stressor as compared to NT with higher sAA increases +1 min and +10 min after TSST cessation ( 128 ). This suggest that the stress-induced physiological hyperreactivity in EHT also extends to the SNS parameter sAA.…”
Section: Resultsmentioning
confidence: 99%
“…In the hitherto only study investigating sAA reactivity to AMS in EHT, we recently found that HT exhibit greater sAA reactivity to the TSST as a strong mental stressor as compared to NT with higher sAA increases +1 min and +10 min after TSST cessation ( 128 ). This suggest that the stress-induced physiological hyperreactivity in EHT also extends to the SNS parameter sAA.…”
Section: Resultsmentioning
confidence: 99%
“…sAA has a faster response to stress than salivary cortisol, and is recently attracting attention as an objective stress assessment method (21,22). Since this response occurs in a short time through directly sympathetic nerve, it occurs in a short period of time, and many reports that take advantage of this characteristic (23)(24)(25). On the other hand, there are also several reports regarding the relationship between chronic stress and sAA(26, 27).…”
Section: Discussionmentioning
confidence: 99%
“…158 CHD patients exhibited insufficient antithrombin recovery poststress. 141 A systematic review 267 of four studies 157 268 269 270 suggests that compared with normotensive controls, patients with systemic hypertension, particularly with diastolic hypertension, show greater stress-induced hypercoagulability, especially during stress recovery. Consistent with this, delayed systolic blood pressure recovery after stress in healthy individuals was associated with delayed recovery of FVIII:C and plasma viscosity.…”
Section: Mechanisms Involved In Stress-induced Hypercoagulabilitymentioning
confidence: 99%